Preview of the ERS Lung Science Conference 2023 and Sleep and Breathing Conference 2023 - Cuevas, Sara, Ocaña (2023)
In this article, we provide a brief description of the @EuroRespSoc 2023 Lung Science Conference and the Sleep and Breathing Conference https://bit.ly/3WsCzj6 Here we provide a preview of the main topics to be addressed in the 2023 Lung Science Conference (LSC) and the Sleep and Breathing Conference, which this year will both have a hybrid format. The LSC is organised by the European Respiratory Society (ERS), while the Sleep and Breathing Conference is organised by ERS and the European Sleep Research Society (ESRS). Both conferences offer early career members (ECMs) the opportunity to network with peers from across the globe, present their work and participate in many activities that will contribute to boost their career in the respiratory field.